Analisis Perbedaan Persepsi Berdasarkan pada Pilihan profesi akuntan - Yusti Pujisari (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2013)
This study aims to empirically examine differences in accounting student motivation is based on the choice of a career as a corporate accountant, government accountants, public accountants and accounting educators. Respondents were students at a college in Yogyakarta who have taken 4 or more semesters. The results showed that the variables of financial rewards, professional training and work market considerations have no differences based on career choices, while variable working environment and social values proved to have a significant difference based on career choices